THE RELATIONSHIP OF SAFETY AND HEALTH MANAGEMENT PRACTICES ON EMPLOYEES’ PERFORMANCE IN MANUFACTURING FIRMS AT PENANG, MALAYSIA - AMIN, BOKHORI MD (International Journal of Multidisciplinary Research and Studies, 2021)
This study evaluated the relationship between welfare management practices, emergency management practices, and safe workplace environment practices on employees' performance in manufacturing firms in Penang, Malaysia. A sample size of 222 respondents was taken from 28 electrical manufacturing firms with a 6322 population and 361 samples to examine the relationship. A questionnaire was designed for data collection to measure welfare management practices, emergency management practices, and safe work place environment practices on employees' performance in manufacturing firms. A stratified sampling method was used, and the data was analyzed using SmartPls 3.7.8. The study showed that welfare management practices, emergency management practices, and safe workplace environment practices significantly affect employees' performance in manufacturing firms. However, the limitation of this study only covers electrical manufacturing firms. Suggested for future study focus on electronic, plastic, and fabricated manufacturing firms to be more effective in improving manufacturing firms' safety and health practices.